The case of Tehran's urban heat island, Iran: Impacts of urban 'lockdown' associated with the COVID-19 pandemic. (December 2021) - Roshan, Gholamreza; Sarli, Reza; Grab, Stefan W.
Highlights: The spatial extent of Tehran's urban heat island is reduced in March-April 2020 due to lockdown. Statistics show that urban cooling in March-April cannot be accounted for by regional synoptics. Strongest March-April negative temperature departures in two decades are recorded for Tehran. Urban diurnal temperature range in Tehran is considerably reduced due to lockdown. Urban cooling due to COVID-19 related lockdown has implications for urban heat management. Abstract: The increasing expansion of urban environments with associated transformation of land-cover has led to the formation of urban heat islands (UHI) in many urbanized regions worldwide. COVID-19 related environmental impacts, through reduced urban activities, is worthy of investigation as it may demonstrate human capacity to manage UHI. We aim to establish the thermal impacts associated with COVID-19 induced urban 'lockdown' from 20 March to 20 April 2020 over Tehran. Areal changes in UHI are assessed through Classification and Regression Trees (CART), measured against background synoptic scale temperature changes over the years 1950–2020. Results indicate that monthly Tmean, Tmax and Tmin values during this time were considerably lower than long-term mean values for the reference period. Although the COVID-19 initiated shutdown led to an identifiable temperature anomaly, we demonstrate that this is not a product of upper atmospheric or synoptic conditions alone. We also show that the cooling effect over Tehran was not spatially uniform, which is likely due to the complexity of land uses such as industrial as opposed to residential. Our findings provide potentially valuable insights and implications for future management of urban heat islands during extreme heat waves that pose a serious threat to human health.